Legal perspectives on the protection of bilateral investment between China and Switzerland. (5th December 2019) - Kölliker, Isabel A.
ABSTRACT: Given the rapid increase of bilateral investments between China and Switzerland over the last decade, the legal framework applicable to foreign investment has become more and more sophisticated reflecting the various interests regarding foreign investment. These interests do not only include the protection and promotion of foreign investment in order to facilitate economic growth, but also the safeguard of the effective functioning of the markets as well as the protection of national security from undue influence by foreign actors. In light of this, this paper takes a comparative law perspective on the applicable legal framework for foreign investment flowing from China to Switzerland and vice versa. By doing so, it focuses on the rights of investors under the bilateral investment treaty concluded between the two countries as well as on two ex ante review mechanisms screening transactions involving foreign investment, this being merger control and national security review. Finally, it analyzes the possibilities of Chinese investors to enter the European Union market through investments made in Switzerland and draws lessons from the Swiss experience for a future bilateral investment agreement between China and the European Union. The paper finds that, with the exclusion of 'letter-box' companies, Chinese and Swiss investors can benefit from a high degree of protection provided in the bilateral investment treaty between the two countries, which can be enforced through investor-state arbitration. The merger review processes in the two countries are largely comparable, except for the fact that the Chinese merger review can potentially be based on non-competition factors. Regarding the safeguard of national security, the two countries adopt very different approaches. While China provides for a review mechanism for individual transactions, Switzerland has conducted a general risk assessment screening all potential transactions in the foreseeable future. The two approaches fit the respective circumstances of the two countries. With respect to access to the European Union market, Chinese investors in Switzerland can expect favorable conditions only regarding very specific sectors, this being civil aviation and insurance. In view of negotiations of a future bilateral investment agreement with the European Union, China could notably consider extending most-favored nation treatment to European Union investors with respect to market access.